Production functions of NCAA men and women water polo matches - Gullikson, J.; Gale, L. R.; Mayberry, J. K.; Kim, J.; Killick, L. (Journal of Sports Analytics, 2023)
Previous research has adapted the use of economic production functions to estimate the scoring production of teams in professional sports. Most of these studies have focused on professional male team sports, most notably, US baseball, basketball, and association football. This study adds to the literature by utilizing a new and distinctive data set of shooting statistics from 88 men`s and 38 women`s NCAA water polo contests to estimate production functions for United States` collegiate water polo games and identify the most important variables for predicting margin of victory in such competitions. The results show that shots on goal, average shot distance, number of counterattacks, quick shots, and efficiency in power play conversions are all significant predictors of goal differentials in men`s contests while shots on goal, average shot distance, counterattacks, and center shots are significant predictors in women`s matches. Previous season win percentage, rebounds, exclusions, and missed shots were not significant predictors in the models. These conclusions confirm and extend previous discriminatory studies of elite international water polo contests.